Depiction of Yama on the kakshasana wall of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Yama is portrayed on the kakshasana (seat back) wall of the Undeshwar Temple. The guardian of justice and ruler of the south direction is portrayed holding a staff and a kamandalu (water pot), while one of his hands makes a varada hasta gesture (of granting boons). He is adorned with jewelry and wears an extensive garland. At the bottom left, a buffalo is depicted.